2018
DOI: 10.1002/pits.22186
|View full text |Cite
|
Sign up to set email alerts
|

High school bystanders motivation and response during bias‐based bullying

Abstract: Bias‐based bullying focused on sexual orientation or gender identity in schools has significant negative implications for the academic, social, and emotional well‐being of students who identify as lesbian, gay, or bisexual, or who are perceived to behave in gender nonconforming ways. Despite empirical support for the influence of bystander behavior can have on school bullying, information about bystander behavior during bias‐based bullying remains limited. Using a thematic narrative analysis, this study analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
(41 reference statements)
0
10
0
Order By: Relevance
“…Two studies did not report the gender identities of their samples (Graybill et al, 2009;, and no studies reported only gender diverse participants in their samples. Among the studies that reported having only cisgender participants in their samples, four studies made an effort to note that they included transgender as an option in their demographic materials, but that no participants indicated they were transgender (António & Moleiro, 2015;Kiperman et al, 2014;Quasha et al, 2014;Williams et al, 2018).…”
Section: Sexual Orientation Sex and Gender Diversitymentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies did not report the gender identities of their samples (Graybill et al, 2009;, and no studies reported only gender diverse participants in their samples. Among the studies that reported having only cisgender participants in their samples, four studies made an effort to note that they included transgender as an option in their demographic materials, but that no participants indicated they were transgender (António & Moleiro, 2015;Kiperman et al, 2014;Quasha et al, 2014;Williams et al, 2018).…”
Section: Sexual Orientation Sex and Gender Diversitymentioning
confidence: 99%
“…Research has documented the effects of the bystander effect, or witnessing others be bullied and victimized while remaining idle (see review in Hymel et al, 2005), on LGBTQ youth who are bullied in school (e.g., Williams et al, 2018). Bystanders' behavior can be characterized into three categories: victim support, passive avoidance, or joining and contributing to the peer victimization (Williams et al, 2018). Bystanders (including school staff) often passively avoid or join in the victimization of LGBTQ students (e.g., Salmivalli et al, 2011;Williams et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…6. 16 items (IV part) -BHISQ integrated subscale "Seeing the situation, fact statement" (also identifying the role of observer), was formed by the authors on the basis of an analysis of the scientific literature: Salmivalli et al (1996), Salmivalli and Voeten (2004), Williams and Guerra (2007), Williams et al (2018), Song and Oh (2017), Brinkman and Manning (2016), Saarento and Salmivalli (2015), Forsberg et al (2014), Gini et al (2008), and BHISQ integrated subscales "Bullying intervention" and "Bullying prevention" also formed by the authors on the basis of an analysis of the scientific literature: Olweus (1994), Björkqvist and Österman (1995), Nadel et al (1996), Österman et al (1997Österman et al ( ), O'Connell et al (1999, Chan (2002), Vaillancourt et al(2003), Orpinas and Horne (2006), Chan and Rauenbusch (2004) and others. 7.…”
Section: Participantsmentioning
confidence: 99%